Synthesis of Copper (II) Oxide Nanoparticles using Vitis vinifera L. Leaf Ex-tract and its Application as a Catalyst in Doebner Reaction - Kurniawan, Felie Virgayani; Cahyana, Antonius Herry; Yunarti, Rika Tri (Makara Journal of Science, 2023)
Plant extracts can be used to synthesize nanoparticle because it is efficient, economical, and friendly to the environment. Copper oxide nanoparticles (CuO NPs) were synthesized using an aqueous fraction of Vitis vinifera L leaf extract and Cu(NO3)2 solution as a precursor. This fraction contains secondary metabolites as a reduction agent and stabilizing agents to formed CuO NPs. CuO NPs can be used as a catalyst in a chemical reaction, one of which is the Doebner reaction, which is a simple and efficient reaction of aniline, aromatic aldehydes, and pyruvic acid under reflux conditions to produce derivatives quinoline-4-carboxylic acid. CuO NPs were effectively used in the Doebner reaction and yielded a product is 79.84%. The CuO NPs characterized by Fourier Transform Infra-Red (FTIR), and X-ray Diffraction (XRD) which showed CuO NPs were formed with a size of 24.39 nm. The product synthesized was characterized by TLC (Thin Layer Chromatography), FTIR, UV-Vis Spectrophotometry, and Liquid Chromatography Mass Spectrometry (LC-MS) and confirmed 2-phenylquinoline-4-carboxylic acid was formed.